2019
DOI: 10.1051/0004-6361/201935811
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on the origin of the elements

Abstract: Manganese (Mn) is a key Fe-group element, commonly employed in stellar population and nucleosynthesis studies to explore the role of SN Ia. We have developed a new non-local thermodynamic equilibrium (NLTE) model of Mn, including new photo-ionisation cross-sections and new transition rates caused by collisions with H and H− atoms. We applied the model in combination with one-dimensional (1D) LTE model atmospheres and 3D hydrodynamical simulations of stellar convection to quantify the impact of NLTE and convect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(117 citation statements)
references
References 77 publications
(128 reference statements)
9
108
0
Order By: Relevance
“…More recently, Sitnova et al (2016) found lower NLTE corrections and therefore weaker -but still non-zero -ionization imbalances for stars in common with Bergemann (2011), which they mainly attributed to the inclusion of high-excitation levels of Ti i in their model atom. Bergemann et al (2019) corroborated the strong NLTE corrections found in the earlier study. Moreover, the authors remark that Mn i transitions at a lower excitation potential of more than 2 eV are not strongly affected by convection -that is 3D effects -and are recommended as 1D NLTE estimator.…”
Section: Titanium (Z = 22)supporting
confidence: 90%
“…More recently, Sitnova et al (2016) found lower NLTE corrections and therefore weaker -but still non-zero -ionization imbalances for stars in common with Bergemann (2011), which they mainly attributed to the inclusion of high-excitation levels of Ti i in their model atom. Bergemann et al (2019) corroborated the strong NLTE corrections found in the earlier study. Moreover, the authors remark that Mn i transitions at a lower excitation potential of more than 2 eV are not strongly affected by convection -that is 3D effects -and are recommended as 1D NLTE estimator.…”
Section: Titanium (Z = 22)supporting
confidence: 90%
“…Meunier et al (2017a) (hereafter M17) have developed one model to isolate RV conv contributions based on the observed non-linear relationship between relative depths and absolute RV blueshifts of spectral lines of a given species (here neutral iron) driven by plasma flow in granules, as described in Gray (2009);Reiners et al (2016); Meunier et al (2017b); Gray & Oostra (2018). The exact physical origin of this observed correlation is non-trivial: a correct description of spectral line formation necessitates the summation of many different line profiles, each formed at different depths in the photosphere, and requires a full threedimensional treatment (e.g., see Nordlund et al 2009;Stein 2012;Cegla et al 2013;Bergemann et al 2019 and references therein). An intuitive (though inexact) understanding of this relationship may be determined by considering a simplified 1D picture: in this model, rising plasma low in the photosphere exhibits strong RV blueshift, while plasma closer to the surface has most of its motion directed tangentially as it merges into intergranular lanes, thus exhibiting less RV blueshift (Dravins et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, Nordlund (1985) for the first time studied the spectral line formation in 3D with NLTE effects in a realistic 3D model atmosphere. Since then, 3D NLTE computations on 3D model atmospheres have been used to compute spectral lines of, for example, lithium (Asplund et al 2003), oxygen (Kiselman & Nordlund 1995;Asplund et al 2004Asplund et al , 2005Pereira et al 2009;Prakapavičius et al 2013;Steffen et al 2015), iron (Lind et al 2017), manganese (Bergemann et al 2019), and barium (Gallagher et al 2020) to determine their abundances in solar and other stellar atmospheres. Recently, forward-modeling of chromospheric lines such as the Ca ii 8542 Å line (Leenaarts et al 2009), the Na i D1 line (Leenaarts et al 2010), the Hα line (Leenaarts et al 2012(Leenaarts et al , 2015, the Mg ii h and k lines (Leenaarts et al 2013), and the Ca ii H and K lines (Anusha & Nagendra 2013;Bjørgen et al 2018) were carried out in 3D NLTE to understand the line formation and to study different chromospheric features that are observed with these lines.…”
Section: Introductionmentioning
confidence: 99%
“…Sukhorukov & Leenaarts (2017) synthesized the Mg ii h and k, Lyα, and Lyβ lines taking the complexities of partial frequency redistribution in 3D NLTE into account. Bergemann et al (2019) modelled different chromospheric lines observed in active regions using 3D NLTE computations. 6302.5 Å lines that are formed in a network region.…”
Section: Introductionmentioning
confidence: 99%